MAXIMUM POWER POINT TRACKING PADA IRADIASI DAN SUHU BERFLUKTUASI BERBASIS FUZZY TYPE-2 - Naafilah Widya Mulya; Novie Ayub Windarko; Rachma Prilian Eviningsih (J-Innovation, 2021)
The potential of solar energy in Indonesia can be utilized as renewable energy and become one of the main alternative energy sources for power generation. The characteristics of solar panels will change depending on radiation levels and temperatures causing the power output of solar panels to fluctuate and become unstable. To reduce oscillations in output power, a study is needed to maximize the output power on solar panels, namely by using the Maximum Power Point Tracking (MPPT) method by using DC - DC circuits in the form of Cuk Converters using fuzzy type 2 controls to get optimal power values on the output. Test results using MATLAB / SIMULINK showed that in model 1 when irradian conditions 1000W / m2 with a temperature of 25 oC using Fuzzy Type 1 the accuracy obtained is 97.5% and using Fuzzy Type 2 the accuracy obtained is 100.2%. In model 2 when irradian conditions 1000 W / m2 with a temperature condition of 40oC using Fuzzy Type 1 the accuracy obtained is 94.3% and using Fuzzy Type 2 the accuracy obtained is 93.1%.